Social segmentation and educational inequity: Challenges of stratification in the modern era - Murillo Rosado, Jodamia Uridisnalda (2025)
Social segmentation has always been present in education, limiting equity and social mobility. Throughout history, socioeconomic differences have defined the availability of educational resources, while the COVID-19 pandemic highlighted the digital divide as a new determining factor in inequality. The objective of this study is to analyze the impact of social segmentation on education, considering how socioeconomic inequality conditions access to learning opportunities and the role of ICT in this context. The research followed a qualitative approach, employing a documentary and analytical research design focused on the critical interpretation of social segmentation and its impact on educational inequity. The results indicate that economic power has become increasingly concentrated within a small percentage of society, making quality education less accessible to the majority of the population. Furthermore, the digital divide has deepened in the most vulnerable sectors, and digitalization accelerated even further during the pandemic, exposing the inadequacies and insufficiencies of both the educational system and its approach. At the same time, it can be concluded that ICT can become a powerful and effective tool against inequality if sufficient investment is made in infrastructure, teacher development programs, and inclusive policies specifically designed for this purpose.